The influence of titanium particles on the functionality of osteocytes in bone remodeling: An In-vitro study - Neibal Almabrok; K.G. Aghila Rani; Waad Kheder; Sausan AlKawas; A.R. Samsudin (PLoS ONE, 2025)
Bone remodeling is a tightly controlled process coordinated by osteocytes, which regulate both bone formation by osteoblasts and bone resorption by osteoclasts. Titanium dioxide (TiO₂) implants are widely used in orthopedic and dental prosthetic rehabilitation, with likelihood of leaching titanium particles, raising concerns about their potential impact on bone cell functions. This study aimed to investigate the influence of TiO₂ microparticles (TiO2-MPs) and nanoparticles (TiO2-NPs) on the functionality of osteocytes. MLO-Y4 cells were treated with varying concentrations of TiO2-MPs or TiO2-NPs for viability studies. Cells were treated with 100 µg/mL TiO2-MPs and TiO2-NPs for 21 days, and conditioned media (CM) was obtained for quantifying sclerostin release using ELISA. Indirect osteocyte-osteoblast co-culture was developed by treating MC3T3-E1cells with CM from cells treated with 100 µg/mL TiO2-MPs and TiO2-NPs. Indirect osteocyte-osteoclast co-culture was developed by treating RAW 264.7 cells with CM and RANKL. Osteocyte-osteoblast co-culture was assayed colometrically for Alkaline Phosphatase, RANKL and OPG using ELISA; and TNF- α, IL − 1ß, OC and Runx2 by qPCR. Mineralization was evaluated using Alizarin and calcium quantification. Osteocyte-osteoclast co-culture was assayed for TRAP and Cat K expression. Viability studies demonstrated 100 µg/ml MPs and NPs as a favorable concentration. Sclerostin release was particle size and time-dependent: TiO₂-MPs group, levels measured were 31.13, 14.86, 13.7, and 23.06 pg/ml over time, indicating a pronounced and sustained release compared to the TiO₂-NPs group, showing 24.3, 10.94, 10.55, and 13.71 pg/ml. Osteocyte-osteoblast co-culture showed high RANKL (1709.88 vs 155.06 pg/ml), TNF- α (16.17 vs 1.07-fold), and IL − 1ß (2.08 vs 0.92-fold) in TiO₂-MPs. ALP (12.64 U/ml) and OPG (471.45 pg/ml) were decreased with less amount of nodules in MPs CM compared to control (ALP: 19.46 U/ml; OPG: 1065 pg/ml) and NPs CM (ALP: 17.95 U/ml; OPG: 645.46 pg/ml). Osteocyte-osteoclast co-culture showed upregulation of TRAP (25.24-fold) and Cat K (10-fold) in MPs CM compared to both control and NPs CM. In conclusion, TiO₂ particles disrupt osteocytes functionality through release of sclerostin and RANKL that inhibit osteoblastogenesis and promote osteoclastogenesis in in-vitro osteocyte-osteoblast and osteocyte-osteoclast co-cultures, with microparticles behaving more harmful than nanoparticles.